2006
DOI: 10.1038/sj.bmt.1705274
|View full text |Cite
|
Sign up to set email alerts
|

Long-term donor health and its relationship with outcome of allogeneic hematopoietic stem cell transplantation

Abstract: Data on long-term follow-up of donors for hematopoietic stem cell transplantation (HSCT) are limited. Donors of 612 adult allogeneic HSCT were studied, at a median of 81 (14-181) months post-HSC donation. Nine donors had severe health problems. Five donors died from aggressive malignancies or terminal illness, at a median of 41 (16-57) months post-donation. Notably, all their recipients had leukemic relapses. In contrast, donors of recipients in remission were all living. This observation might be due to an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Obviously with older age the chance for occult malignancy increases. It has been reported that recipients of HSCT from donors who developed cancer after stem cell donation are associated with a higher relapse rate in the recipient [18].…”
Section: Donor Eligibilitymentioning
confidence: 99%
“…Obviously with older age the chance for occult malignancy increases. It has been reported that recipients of HSCT from donors who developed cancer after stem cell donation are associated with a higher relapse rate in the recipient [18].…”
Section: Donor Eligibilitymentioning
confidence: 99%